Performance Analysis of 5-Phase Multi-level Inverter Using Carrier Based PWM Technique - M. Lavanya; B. Jyothi (International Journal of Applied Power Engineering (IJAPE), 2016)
The major analysis has been based on the induction machine drive system that is for the analysis of the carrier based PWM two level source inverter. The unbalanced conditions are mainly to handle the results of simulation for the analysis that results in the two fault conditions. The system setup has been involving the voltage source inverter as well as the five phase multi-level inverter. The effects are through performing the scenarios which consider the performance effects with the load on induction machine. The simulation is based on the imbalance conditions which results on the oscillations depending on the electromagnetic torque through the attendant reduction of the torque rating. The larger slipping has been in the rotor speed.